If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + (-15d + 1) = 2(7d + -16) + -1d Reorder the terms: 5 + (1 + -15d) = 2(7d + -16) + -1d Remove parenthesis around (1 + -15d) 5 + 1 + -15d = 2(7d + -16) + -1d Combine like terms: 5 + 1 = 6 6 + -15d = 2(7d + -16) + -1d Reorder the terms: 6 + -15d = 2(-16 + 7d) + -1d 6 + -15d = (-16 * 2 + 7d * 2) + -1d 6 + -15d = (-32 + 14d) + -1d Combine like terms: 14d + -1d = 13d 6 + -15d = -32 + 13d Solving 6 + -15d = -32 + 13d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-13d' to each side of the equation. 6 + -15d + -13d = -32 + 13d + -13d Combine like terms: -15d + -13d = -28d 6 + -28d = -32 + 13d + -13d Combine like terms: 13d + -13d = 0 6 + -28d = -32 + 0 6 + -28d = -32 Add '-6' to each side of the equation. 6 + -6 + -28d = -32 + -6 Combine like terms: 6 + -6 = 0 0 + -28d = -32 + -6 -28d = -32 + -6 Combine like terms: -32 + -6 = -38 -28d = -38 Divide each side by '-28'. d = 1.357142857 Simplifying d = 1.357142857
| -4+p=-2 | | (3x+5)(x-6)=5x+10 | | -2(-3+7x)=6 | | 24x-3=45 | | -5n-5(n-7)=32-7n | | -5x-4=92+3x | | -12x+8=-2 | | x(2-7)=20 | | -2x+6=-60+4x | | -12+8=-2 | | 9+4x-17=12 | | 3x+185=180 | | 3x/7=-4/9 | | -10+x=-6x-80 | | 4m+3m+8=12 | | 5x43/10 | | 14=x-3x-4 | | 2x+90+x+95=180 | | 5t-1=t/3-17 | | -4+(-2+1)+5-(3-(1-2)+4)+1-2= | | 12X=4X-60 | | 4z/7-5=10 | | -7x+10-3x=-10 | | -w^2+6w-9=0 | | 196x^2y+80x^3+120y^2x= | | 70+80=180 | | X^2+14x=176 | | 51=7x+3x+1 | | (-7*28)+(-7*75)=-7(28+r) | | 3k^2-10k-18=-6k^2+3 | | 110=5y^2+20 | | v^2+6=86 |